Teaching programming and computational thinking in early childhood education: a case study of content knowledge and pedagogical knowledge - Zeng, Yue; Yang, Weipeng; Bautista, Alfredo (Frontiers in Psychology, 2023)
Programming and computational thinking (CT) have been progressively incorporated into early childhood education to prepare children for the digital age. However, little is known about the content knowledge (CK) and pedagogical knowledge (PK) possessed by early childhood teachers in this domain. To address this gap, we conducted a case study of an early childhood teacher in China who had experience developing and implementing an unplugged programming and CT curriculum. The triangulation of data sources was established to collect evidence from videotaped observations, interviews, and lesson plans. For the CK, analysis of these findings revealed that the teacher had a more robust understanding of CT concepts (e.g., sequences, conditionals, and loops) compared to CT practices (e.g., decomposition, debugging) and CT perspectives (e.g., perseverance, choices of conduct). In terms of PK, the teacher could apply the general pedagogical knowledge but was relatively weak in using content-specific pedagogical knowledge. As the first endeavor to investigate an early childhood teacher's CK and PK in teaching programming and CT, this study provides significant implications for improving teachers' professional knowledge and teaching effectiveness in this burgeoning area.